DETERMINATION OF ECONOMIC SELECTION INDEX COEFFICIENTS FOR DAIRY COWS - Sanjin, Ivanović; Dragan, Stanojević; Lana, Nastić; Jeločnik, Marko (Economics of Agriculture, 2014)
There is no research regarding economic effects of genetic improvement for dairy cattle in Serbia. Therefore, the goal of this paper is to determine economic values for various production traits (milk yield, milk fat content and proteins content) in dairy production, as well as to determine total economic selection index. The research is based on data which include 9,516 lactations of 4,893 milking cows from 7 farms. Data were collected during the period 2004 – 2012. Authors used sensitivity analysis and partial budgeting approach to determine changes in revenues caused by variations of particular production traits. It was determined that within economic selection index the most important trait is milk yield, while values for other traits are almost negligible. On the other hand, it is expected that importance of certain traits will be changed after Serbian accession to the European Union.